DNA Diagnostics for Schistosomiasis Control - Weerakoon, Kosala G. (Trop Med Infect Dis, 2018)
Despite extensive efforts over the last few decades, the global disease burden of schistosomiasis still remains unacceptably high. This could partly be attributed to the lack of accurate diagnostic tools for detecting human and animal schistosome infections in endemic areas. In low transmission and low prevalence areas where schistosomiasis elimination is targeted, case detection requires a test that is highly sensitive. Diagnostic tests with low sensitivity will miss individuals with low infection intensity and these will continue to contribute to transmission, thereby interfering with the efficacy of the control measures operating. Of the many diagnostic approaches undertaken to date, the detection of schistosome DNA using DNA amplification techniques including polymerase chain reaction (PCR) provide valuable adjuncts to more conventional microscopic and serological methods, due their accuracy, high sensitivity, and the capacity to detect early pre-patent infections. Furthermore, DNA-based methods represent important screening tools, particularly in those endemic areas with ongoing control where infection prevalence and intensity have been reduced to very low levels. Here we review the role of DNA diagnostics in the path towards the control and elimination of schistosomiasis.